Validasi Terhadap Multimedia Interaktif Powerpoint Pada Pembelajaran Tematik Terpadu Sekolah Dasar: Validation Of Powerpoint Interactive Multimedia in Integrated Thematic Learning in Elementary Schools - Yenni Atikah Pane Tika; Yanti Fitria (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This study aimed to determine the validity level of powerpoint interactive multimedia in integrated thematic learning for class V elementary school. This study used the Research and Development (R&D) method. The results showed that powerpoint interactive multimedia in integrated thematic learning was stated to be very valid with the assessment of material experts 84.54%, 89.5% linguists, and media experts 81.67% with an overall validator average score of 85.23% with category “very valid”. Based on the results of the study, it can be concluded that powerpoint interactive multimedia in integrated thematic learning for class V elementary school “very valid” is used in the learning process.